Spirituality and Religion as Coping Mechanisms: Families Raising Children with Developmental Disabilities - Shackell, Erin M.A. (Université Saint-Paul / Saint Paul University, 2011)
The process of rearing a child with a developmental disability is arguably difficult for many families, yet there appears to be some families and parents who cope more easily with their child’s disability. Two additional factors, which have been identified as coping resources and have become rather popular in the realm of resiliency research, are spirituality and religiosity. The study sought to address the hypothesis that aspects of spiritual well-being as measured by the Holistic Spirituality Model (Rovers & Kocum, 2010) would predict better familial coping beyond the contribution of other demographic and psychosocial factors. Additionally this study was addressing the hypothesis that other previously significant psychosocial variables would become less predictive of familial ability to cope with the addition of spirituality and religiosity to the model. Lastly it was predicted that individual subscales of the Holistic Spirituality Model would correlate with better scores on the Questionnaire on Resources and Stress which measured the family’s ability to cope with raising a child with a developmental disability. This study is a replication of a previous study conducted by Jones and Passey (2004), with the addition of the Holistic Spirituality Model developed by Rovers and Kocum (2010). A hierarchical regression analysis was conducted, blocking variables by questionnaire while controlling for specific demographic variables. Results suggest no support for the first two hypotheses. A positive correlation was found between the existential well-being subscale of the Holistic Spirituality Model and the Questionnaire on Resources and Stress which measured familial coping while raising a child with a developmental disability.
Keywords: Disability; Coping; Sprituality; Religion